Combined effect of calcium chloride and aloe mucilage on postharvest quality of spine gourd (Momordica dioica Roxb.) fruits - Bhardwaj, R.L.; Choudhary, K.; Priyanka; Hingonia, Kiran; Sharma, Anita; Meena, Jaydeep (Indian Journal of Horticulture, 2024)
To observe the response of fruit coating by edible calcium chloride and aloe mucilage on the physicochemical quality and storability of spine gourd fruits. The three levels of calcium chloride (CaCl2) (10, 20 and 30%) and aloe mucilage (10, 20 and 30%) were possibly combined for experimentation in three replications with untreated fruits as control. Fresh spine gourd fruits, treated with 30% of CaCl2 and aloe mucilage, showed significantly lower values of physiological loss in weight, fruit decay, colour development of fruits. In contrast, higher titratable acidity values and shelf-life duration were also in the same treatment. On the contrary, fruit firmness was retained at the higher side and total soluble solids at the lower level, when fruits were treated with 30% of CaCl2 in combination with 20% aloe mucilage. In the same treatment, marketability of the fruits was highest (91.30, 68.48 and 10.06%) than those treated with other concentrates at the 3rd, 6th and 9th day of storage, respectively. Therefore, observations suggested that application of CaCl2 (30%) in combination with aloe mucilage at 30%, the shelf-life of spine gourd fruit can be extended up to 6 days with retention of fruit quality under ambient conditions.